Seroprevalence of toxoplasmosis in voluntary blood donors of Puducherry and surrounding districts of Tamil Nadu - Stephen, Selvaraj (J Parasit Dis, 2017)
Our objective is to study the seroprevalence of toxoplasmosis in the voluntary blood donors of Puducherry and surrounding districts of Tamil Nadu. A total of 275 healthy blood donors were screened for the presence of IgM and IgG antibodies to Toxoplasma gondii by ELISA test. Donor samples positive for IgM and/or IgG antibodies to T. gondii were subjected to IgG avidity ELISA. While, 54 out of 275 donors had IgG antibodies (19.66%), only one donor had IgM (0.36%) along with IgG. Among 54 IgG positive donors, only two had low avidity (3.7%), indicating recent exposure to the protozoa. Feasibility and cost effectiveness studies should be conducted throughout India to decide regarding screening of blood donors for toxoplasmosis.